Isolation and Characterisation of PRSV-P Resistance Genes in Carica and Vasconcellea - M. R. Razean Haireen; R. A. Drew (International Journal of Genomics)
Papaya (Carica papaya L.) is one of the major tropical fruit crops worldwide, but it is limited throughout its range by papaya ringspot virus type P (PRSV-P). Previous genetic studies identified a functional PRSV-P resistance marker in a mapping population of F2 plants of Vasconcellea pubescens (resistant to PRSV-P) × Vasconcellea parviflora (susceptible to PRSV-P) and showed that the marker exhibited homology to a serine threonine protein kinase (STK) gene. Full length cDNAs of putative PRSV-P resistance genes designated CP_STK from C. papaya and VP_STK1 and VP_STK2 from V. pubescens were cloned by rapid amplification of cDNA ends (RACE). Due to a frame-shift mutation, the two homologous sequences are transcribed and edited differently such that the gene product in V. pubescens is two separate transcripts, whereas in C. papaya they are fused into a single message. A peroxisomal targeting signal (PTS2) present in VP_STK2 but absent in the other transcripts may be the functional source of PRSV resistance in V. pubescens. The STK gene from V. pubescens may have been derived from an alternative splicing to confer resistance. The putative resistance gene, VP_STK2, that was identified in this study is a potential new source of PRSV-P resistance for papaya genotypes.